PENGARUH K-POP DALAM ADAPTASI FASHION ISLAMI DAN DAKWAH DIGITAL DI KALANGAN MAHASISWA UINSA: INDONESIA - keluarga baday, dwiyan adji masduki (Universitas Islam Syekh-Yusuf, 2024)
This research examines how UINSA female students adapt Islamic fashion with the influence of Korean pop culture (K-pop), creating a modern style that still complies with religious rules. They incorporate elements such as modern hijab and oversized sweaters, and utilize social media to create relevant da'wah content for the younger generation. This study shows that Kpop is not just entertainment, but also has the potential to be an effective creative da'wah medium in integrating popular culture with religious values.